Lithostratigraphy of Paleozoic Carbonates in the Kinta Valley, Peninsular Malaysia: Analogue for Paleozoic Successions - Haylay Tsegab, Chow Weng Sum, Jasmi Ab Talib, . (2017)
Tectonics of the Paleo-Tethys resulted in the formation of three distinct stratigraphic zones in Peninsular Malaysia, namely western, central, and eastern zones. The western zone encompasses extensive carbonate sediments, among which is the Kinta Limestone, which forms a major Silurian to Permian lithological unit. Subjection to diagenetic and thermal alteration of this succession and paucity of unweathered and accessible outcrop sections posed constraints on precise characterization of lithofacies